Assessment of micronutrients fractionations and mobility in soils of eastern Uttar Pradesh - PATRA, ABHIK; SINGH, SATISH KUMAR; JATAV, SURENDRA SINGH; REKWAR, RAVINDRA KUMAR (The Indian Journal of Agricultural Sciences, 2021)
In the present investigation, an attempt has been made to assess the various chemical forms and mobility factor (MF) for zinc (Zn), copper (Cu), iron (Fe) and manganese (Mn) in different soils of eastern Uttar Pradesh. For this purpose, surface soil (0-15 cm) samples from two different locations were collected under Entisol, Inceptisol, Vertisol and Alfisol during 2019-20 and analysis was done in the laboratory of Department of Soil Science and Agricultural Chemistry, BHU, Varanasi. The modified Tessier sequential extraction procedure was used to determine the chemical pools of Zn, Cu, Fe and Mn in each soil. Results indicated that total metal content follows the order of Fe>Mn>Zn>Cu across the soil orders, whereas mobility factor of micronutrients arranged as: Mn>Cu>Zn>Fe. The highest exchangeable (F1), carbonate bound (F2), Fe-Mn oxides bound (F3), organically bound (F4) and residual (F5) fraction were recorded in Inceptisol, Vertisol, Alfisol, Inceptisol and Alfisol, respectively for micronutrients, i.e. Zn, Cu, Fe and Mn. The mean percentage value of various micronutrients fractions were in the order of F5>F3>F4>F2>F1, except Mn, whose chemical forms follows the order of F3>F5>F4>F2>F1. The Zn and Cu were highly mobile in Vertisol while Fe and Mn in Entisol.